Proposal of an On-demand Software Deployment System Based on Application Streaming, Virtualization Techniques and P2P Transport - Teixeira, Rafael Augusto [UNESP]; Cavenaghi, Marcos Antônio [UNESP]; Lobato, Renata Spolon [UNESP]; Lobato, Renata Spolon [UNESP] (Springer Nature, 2010)
This paper presents the work in progress of an on-demand software deployment system based on application virtualization concepts which eliminates the need of software installation and configuration on each computer. Some mechanisms were created, such as mapping of utilization of resources by the application to improve the software distribution and startup; a virtualization middleware which give all resources needed for the software execution; an asynchronous P2P transport used to optimizing distribution on the network; and off-line support where the user can execute the application even when the server is not available or when is out of the network. © Springer-Verlag Berlin Heidelberg 2010.
Keywords: application streaming; Application virtualization; middleware; sequencing; software deployment; Application streaming; Software deployment; Software distributions; Software installations; Utilization of resources; Virtualization Techniques; Application programs; Middleware; Virtual reality; Peer to peer networks